Mechanisms of Epidermal Growth Factor Effect on Animal Intestinal Phosphate Absorption: A Review - Tang, Xiaopeng; Liu, Xuguang; Liu, Hu (Frontiers in Veterinary Science, 2021)
Phosphorus is one of the essential mineral elements of animals that plays an important role in animal growth and development, bone formation, energy metabolism, nucleic acid synthesis, cell signal transduction, and blood acid–base balance. It has been established that the Type IIb sodium-dependent phosphate cotransporters (NaPi-IIb) protein is the major sodium-dependent phosphate (Pi) transporter, which plays an important role in Pi uptake across the apical membrane of epithelial cells in the small intestine. Previous studies have demonstrated that epidermal growth factor (EGF) is involved in regulating intestinal Pi absorption. Here we summarize the effects of EGF on active Pi transport of NaPi-IIb under different conditions. Under normal conditions, EGF inhibits the active transport of Pi by inhibiting the expression of NaPi-IIb, while, under intestinal injury condition, EGF promotes the active absorption of Pi through upregulating the expression of NaPi-IIb. This review provides a reference for information about EGF-regulatory functions in Pi absorption in the animal intestine.